Three new additions to the Cyperaceous Flora of Nepal - Paneru, D.; Joshi, L.R.; Adhikari , B.; Rajbhandary, S. (Rheedea, 2024)
Three species of Cyperaceae, Fimbristylis naikii Wad.Khan & Lakshmin., Schoenoplectiella praelongata (Poir.) Lye and Scleria psilorrhiza C.B.Clarke ex Hook.f. , are reported from Nepal for the first time from Shuklaphanta National Park in Kanchanpur district. A detailed description, distribution notes and photographs for each species are provided.